2015
DOI: 10.1177/2333794x15607798
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age, Gender, and Addition of Probiotics on Treatment Success for Helicobacter pylori in Children

Abstract: The primary objective of this study was to evaluate the effect of age, gender, and the use of probiotics with standard treatment regimen on Helicobacter pylori eradication. Based on endoscopic findings and clinical presentation, selected patients were treated with standard triple therapy (omeprazole, clarithromycin, and amoxicillin). Those who failed were offered a repeat treatment with omeprazole, metronidazole, and amoxicillin. After the publications of the possible advantages of probiotic treatment on H pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…A larger sample with more patients and physicians is needed for more accurate investigation. Second, the study could have assessed other factors that were previously reported to affect outcome of eradication therapy, such as smoking, alcohol use, and use of combined probiotics . These factors could not be controlled because we conducted a retrospective review of the patients’ medical records.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A larger sample with more patients and physicians is needed for more accurate investigation. Second, the study could have assessed other factors that were previously reported to affect outcome of eradication therapy, such as smoking, alcohol use, and use of combined probiotics . These factors could not be controlled because we conducted a retrospective review of the patients’ medical records.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the study could have assessed other factors that were previously reported to affect outcome of eradication therapy, such as smoking, alcohol use, and use of combined probiotics. [19][20][21]28 These factors could not be controlled because we conducted a retrospective review of the patients' medical records. Third, drug adherence was insufficiently assessed because we could not establish whether they had forgotten to take the drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for these contradictory results may be due to the small number of studies with a subgroup analysis on children . Unlike the results found in adults, a probiotics compound can notably increase eradication rates in children in second‐line treatment (omeprazole, amoxicillin and metronidazole for 14 days; 72% vs 45%, P = 0.053) …”
Section: Probiotics For H Pylori Eradication Treatment In Childrenmentioning
confidence: 95%
“…However, a recent meta-analysis including 10 randomized studies showed that in 318 of 409 (78%) children who received a sequential treatment, the infection was eradicated compared with 314 of 444 (70.7%) in the triple therapy arm (RR 1.14, 95% CI 1.06-1.23) [101]. Weiner and Shaoul [122] evaluated the efficacy of a triple therapy containing clarithromycin for 14 days as first-line treatment and containing metronidazole as rescue treatment. Antimicrobial susceptibility was not tested, and a comparison was made between those receiving the triple therapy alone and those receiving a probiotic.…”
Section: Treatmentmentioning
confidence: 99%